'I'm dealing with all these health issues that could have been addressed when I was younger'. Delivery of health services to Australian young people in out‐of‐home care: Lived experiences. (19th August 2021) - Smales, Madelaine; Morris, Heather; Savaglio, Melissa; Skouteris, Helen; Green, Rachael
Abstract: Care‐experienced young people demonstrate significantly poor physical, social and mental health outcomes during and beyond their time in care, yet they have rarely been consulted or included in research examining their health needs to date. This qualitative paper explores care‐experienced young people's perceptions of health in care, including accessing healthcare and interacting with health professionals. The research methodology was informed by a co‐design approach through consultation with care‐experienced young people. Semi‐structured interviews were conducted with 10 young people. The findings revealed that: (1) the care system does not nurture young people's health; (2) young people in care experience difficulty accessing and navigating a complex health system; and (3) young people are not given a voice when it comes to their health. The findings provide key recommendations for practice, including the empowerment of young people through positive, responsive and trusting relationships to prioritise the health of young people in care.